2001
DOI: 10.1016/s0378-1097(01)00247-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous mutations affecting transcriptional regulation by protocatechuate in Acinetobacter

Abstract: Positive selection yields Acinetobacter strains with a spontaneous mutation blocking catabolism of protocatechuate. For this study, the growth temperature during selection was lowered to 22³C: growth at 37³C was found to mask the role of the protocatechuate-responsive transcriptional regulator PcaU. The resulting mutants included those with amino acid substitutions useful for understanding PcaU structure and function, a 20-bp deletion whose repeated isolation suggested genetic instability of DNA in the putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Indication for a physiological function of these external sequence repetitions comes from the observed growth phenotypes of two spontaneous mutant strains, one containing a C3T base substitution within the external sequence repetition and the second one with a deletion of the direct sequence repetition. The respective strains show a cold-enhanced block in protocatechuate catabolism (7,42). Thus both PcaU binding and gene expression are impaired when one of the external sequence repetitions is modified or deleted, and possibly pca gene expression is not inducible at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indication for a physiological function of these external sequence repetitions comes from the observed growth phenotypes of two spontaneous mutant strains, one containing a C3T base substitution within the external sequence repetition and the second one with a deletion of the direct sequence repetition. The respective strains show a cold-enhanced block in protocatechuate catabolism (7,42). Thus both PcaU binding and gene expression are impaired when one of the external sequence repetitions is modified or deleted, and possibly pca gene expression is not inducible at all.…”
Section: Discussionmentioning
confidence: 99%
“…Both fragments contain three sequence repetitions; it has been suggested that these are recognized and bound by PcaU (17). A first indication that full transcriptional activation requires the presence of all three sequence repetitions comes from the recent identification of spontaneous mutations in the pcaU-pcaI intergenic region (7). Nothing is known about the way in which PcaU interacts with this unusual potential binding site and how communication with RNA polymerase is accomplished.…”
mentioning
confidence: 99%
“…In one study, a quarter of the spontaneous mutations were deletions, and some of them extended into neighboring genes (18). The discovery that some of the deletions upstream of the pca structural genes eliminated the ability of strains to grow on the six-carbon dicarboxylic acid, adipic acid, provided the first evidence for linkage of adipate utilization genes and pca genes (10,11).…”
mentioning
confidence: 99%
“…PcaU may be involved in a regulon whose target genes have yet to be fully characterized. Sequence similarities between the PcaU and PobR regulators have led to speculation that these two regulators, like BenM and CatM, have overlapping or interconnected functions (9,21,39).…”
Section: Discussionmentioning
confidence: 99%